PERGESERAN NILAI-NILAI DEMOKRASI: SEBUAH REFLEKSI PASCA BERGULIRNYA DANA DESA - Dheni Irawan (Muhammadiyah Law Review Journal, 2020)
The purpose of this research is to look at the shift of the village community in terms of democracy, which was originally from a consensus in determining the village head to be a practical political practice for the village community, without thinking about the consequences that will be felt in the future. The revolving of village funds for development and community empowerment is one factor shifting democratic values. The method in this research is normative juridical. This research shows that developing democratic life in the village is an obligation for the village as a consequence of autonomy, where in the concept of autonomy the given authority is interpreted as a responsibility to accelerate the welfare of the community through improving the democratic system. However, the principles of democracy applied in villages must be developed in accordance with the principles of recognition and subsidiarity based on the socio-cultural village. So that the implementation and development of democratic life in the village is not only done for the sake of democracy itself, but is oriented towards the collective progress of the village community.